(untitled) (SAARC Journal of Agriculture, 2023)
Success stories that encompass entirely from callus induction to fruit bearing of tomato are very limited. Here, this study uncovers an optimized protocol for in vitro regeneration of BARI Tomato-15 which successfully leads to fruit bearing. First leaf and epicotyls were used as explant in MS medium with different concentrations of Indol-3 acetic acid (IAA) and 6-Benzyl amino purin (BAP) for regeneration. MS media containing 0.5 mg L-1 IAA + 0.5 mg L-1 BAP and 0.5 mg L-1 IAA + 2.0 mg L-1 BAP performed best and exhibited the highest frequencies of callus formation and regeneration from first leaves and epicotyl. A combination of 0.5 mg L-1 BAP and 0.5 mg L-1 IAA exhibited the longest shoot (11.33 cm) and root (7.00 cm) length at in vitro conditions. Plants derived from the same combination produced the highest number of leaves (22) and plant height (8.33 cm), and accelerated early flowering and increased fruit bearing (134-plant) with satisfactory yield (5.71 kg-plant) after acclimatization at field condition. Therefore, MS media containing 0.5 mg L-1 IAA + 0.5 mg L-1 BAP could be an effective combination for regeneration and development of an early maturing tomato cultivar. SAARC J. Agric., 21(1): 89-101 (2023)